FRI0439 Beliefs, health status and outcomes in patients undergoing total knee arthroplasty. Prospective study with 12 months followup. (23rd January 2014) - Nuñez, M.; Nuñez, E.; Sastre, S.; Lozano, L.; Saulό, A.; Nicodemo, C.; Segur, J.M.; Maculé, F.
Abstract : Background: Previous studies report that between 17-30% of patients are not satisfied with the outcome after undergoing total knee arthroplasty (TKA), believing that their pain or functional disability would improve more or that the recovery would be less difficult. Beliefs are motivators of behaviour, with the cognitive component, i.e. what the person knows or thinks they know, being one of the main factors. It has been reported that, in musculoskeletal diseases, the degree of behavior/adherence (recommendations agreed between the practitioner and patient) to therapeutic regimens is often low, thereby reducing efficacy. In TKA, where active patient participation in therapy is required, a high level of adhesion is necessary to obtain good results. Therefore, determining the extent to which patients believe that their behavior can influence TKA outcomes is of interest. Objectives: To determine whether the belief that behavior influences the health status is associated with better outcomes in terms of quality of life in patients with knee osteoarthritis twelve months after TKA. Methods: A prospective study with 12 months follow-up. Sociodemographic and clinical variables were collected. Patient's opinions on the influence of their behavior on TKA outcomes were measured using the question "Do you think your behavior can affect your health status?" with 5 response categories (Likert scale): 1 totally agree; 2 agree somewhat; 3 do not know: 4 disagree somewhat: 5 strongly disagree. The health status was assessed using the SF-36 and WOMAC questionnaires. A multinomial logit model was constructed. Results: 98 patients, mean age 70.3 years (SD 7.2), 82% female, 75% with low education, body mass index (BMI) 32.74 (SD 5.6), were included. 57% said they did not know and 15% strongly disagreed that they believed behaviour could influence the health status. The multinomial logit model showed that patients who disagreed that their behavior could affect their health had worse scores in the physical and mental SF-36 components and total WOMAC score (p<0.02) 12 months after TKA. Age, sex and BMI were not significantly associated with any of the behavioural categories considered. Conclusions: The cognitive element of beliefs about the influence of behavior on health was very low. Patients who believed that their health depends on their behavior had better outcomes (SF-36 and WOMAC scores) 12 months after TKA than those who do not. This shows the importance of beliefs and the need for health professionals to design educational strategies to reinforce them in order to promote behaviours that improve therapeutic outcomes. This study was funded by Spanish Ministry of Health grant FIS PS09/01148 References: Mason JB. The new demands by patients in the modern era of total joint arthroplasty: a point of view. Clin Orthop Relat Res 2008;466(1):146-52. Franklin PD, Li W, Ayers DC. The Chitranjan Ranawat Award: functional outcome after total knee replacement varies with patient attributes. Clin Orthop 2008;466:2597–2604. Disclosure of Interest: None Declared